EP.WE.197Feasibility of a remotely supervised exercise programme. (28th October 2021) - Machin, Matthew; Hayward, Laura; Harris, Lindsey; Gadhvi, Vijay; Thapar, Ankur
Abstract: Aim: To assess feasibility of a novel remotely-supervised exercise programme at a vascular hub during the COVID-19 lockdown. Methods: Participants with arterial claudication (ABPI <0.90) who were able to walk 50m were enrolled into a 3-month programme by a vascular specialist nurse. The initial appointment addressed smoking cessation and best medical therapy. Baseline walking distance, ABPI and quality of life (QoL) were measured using the Intermittent Claudication Questionnaire. Following this, up to 8 WhatsApp video calls with a vascular specialist physiotherapist were undertaken to provide a tailored exercise programme. The Mapmywalk© App, or a pedometer, were used to monitor walking distances. Participants were instructed to record their daily longest walk and email results to their physiotherapist before each consultation. Results: 12 participants were enrolled, of these 2 participants were unsuitable. Median age was 63 years and 2 (20%) were female. Baseline median ABPI was 0.7 (IQR 0.5-0.8), median baseline absolute walking distance was 75m (IQR 50-140) and median baseline QoL was 51/80 (IQR 15-79). 7 participants (70%) successfully completed the programme and were discharged. Their median daily longest walk was 2000m (IQR 200-4000) and QoL scores improved to 6/80 (IQR 2-20) (p = 0.02). Remaining 3 participants required revascularisation for disease progression. Reimbursement tariffs for the supervised exercise programme were £700 per patient, whereas for revascularisation were £2000 - £5000. Conclusion: Remotely supervised exercise was feasible and improved walking distance and quality of life in 70% of participants. Approximately £3000 per patient was saved from a reduction in revascularisation procedures in our unit.